PERAN WORK-LIFE BALANCE DALAM MENINGKATKAN EMPLOYEE ENGAGEMENT DAN KINERJA KARYAWAN PT TASPEN (PERSERO) - Lobo, Kevin; Vincent Didiek Wiet Aryanto (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
This study aims to analyze the effect of Work Life Balance (WLB) on Employee Performance, both directly and indirectly through Keterlibatan karyawan (EE) as a mediating variable at PT TASPEN (Persero). The research employs a quantitative explanatory approach using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Primary data were collected from 80 permanent employees using a closed-ended questionnaire with a five-point Likert scale. The research instrument encompasses three main variables: WLB, EE, and Employee Performance, with a total of 10 indicators. The outer model analysis indicates that all indicators are valid and reliable. The inner model analysis shows that WLB has a significant effect on both EE and Performance. Furthermore, EE is proven to mediate the relationship between WLB and Performance. High values of R² and Q² demonstrate strong predictive power and model relevance. These findings support the Spillover and Enrichment theories and highlight the importance of keseimbangan kerja dan kehidupan pribadi and emotional engagement in enhancing employee performance within public sector organizations.